Variation in Membrane Trafficking Linked to SNARE AtSYP51 Interaction With Aquaporin NIP1;1 - Barozzi, Fabrizio; Papadia, Paride; Stefano, Giovanni; Renna, Luciana; Brandizzi, Federica; Migoni, Danilo; Fanizzi, Francesco Paolo; Piro, Gabriella; Di Sansebastiano, Gian-Pietro (Frontiers in Plant Science, 2019)
SYP51 and 52 are the two members of the SYP5 Qc-SNARE gene family in Arabidopsis thaliana. These two proteins, besides their high level of sequence identity (85%), have shown to have differential functional specificity and possess a different interactome. Here we describe a unique and specific interaction of SYP51 with an ER aquaporin, AtNIP1;1 (also known as NLM1) indicated to be able to transport arsenite ( As(III) ) and previously localized on PM. In the present work we investigate in detail such localization in vivo and characterize the interaction with SYP51. We suggest that this interaction may reveal a new mechanism regulating tonoplast invagination and recycling. We propose this interaction to be part of a regulatory mechanism associated with direct membrane transport from ER to tonoplast and Golgi mediated vesicle trafficking. We also demonstrate that NIP1;1 is important for plant tolerance to arsenite but does not alter its uptake or translocation. To explain such phenomenon the hypothesis that SYP51/NIP1;1 interaction modifies ER and vacuole ability to accumulate arsenite is discussed.